Geographical distribution of Biomphalaria snails in the State of Minas Gerais, Brazil - Souza Cecília Pereira de; Caldeira Roberta Lima; Drummond Sandra Costa; Melo Alan Lane; Guimarães Carlos Tito; Soares Delza de Moura; Carvalho Omar dos Santos (Memorias do Instituto Oswaldo Cruz, 2001)
Published and unpublished observations on geographical distribution of Biomphalaria snails in the State of Minas Gerais, Brazil, were compiled. This work is aimed at knowing the present occurrence of Biomphalaria species in this region, and at contributing to the elaboration of the planorbid chart of Minas Gerais. In malacological surveys, performed by several researchers, the presence of seven species of this genus was recorded. Those planorbids were found in 12 mesoregions, in 283 (33.1%) municipalities out of 853 with the following distribution: B. glabrata (185 municipalities), B. straminea (125), B. tenagophila (58), B. peregrina (57), B. schrammi (26), B. intermedia (20) and B. occidentalis (2). B. glabrata and B. tenagophila are found naturally infected by Schistosoma mansoni in Minas Gerais. In 24 municipalities the three snail hosts of S. mansoni in Brazil, B. glabrata, B. tenagophila and B. straminea, are present.